Kontribusi Laboratorium Pendidikan Agama Islam dalam Materi Perawatan Jenazah - Suparwoto Sapto Wahono; Dinik Nurul Fuadah (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2021)
The process of treating corpses requires skill, therefore repeated experience is needed. The existence of a laboratory is very important, both used in the introduction of material in theory and practice. In practice, the care of corpse requires learning resources, teaching aids and so on to support the implementation of corpse care practices. This study aimed to determine the existence of the PAI laboratory seen from the conditions, management and use of the PAI laboratory in the practice of corpse care materials. The method in this study used a descriptive qualitative approach. The results showed that the conditions of the PAI laboratory met the comfort requirements of the PAI laboratory. The PAI Laboratory management has an organizational structure and is in charge of the PAI laboratory inventory. The use of PAI laboratory in the practice of caring for corpses was carried out in semester 4 (four), namely class 2 even semester. In the implementation of the practice of caring for the corpse, it began with